Políticas públicas de economia solidária no município de São Carlos-SP, de 2001 a 2011 - Meireles, Eduardo (2012)
The solidarity economy is born in Brazil in the late 80's and early 90's historical struggles of social movements as well as municipal administrations initiatives against unemployment and poverty, compounded on the axis of the work to include persons historically excluded by the hegemony capitalist economic. It comes as an alternative income generation and economic and social inclusion. For this reason, and given the importance of this issue from the standpoint of economic and social, many municipalities have invested in developing initiatives to promote the solidarity economy, these initiatives vary according to locality and region and can range from simple actions public policies, since this work was. Objective: to present to the public policies that promote the social economy of São Carlos-SP, key actions and actors, as well as understand their construction and analyze the actual content of that policy, ie, programs, policies, structures and support to public enterprises solidarity economy. Method: case study, after the fact in a descriptive and explanatory, the strategy chosen when examining contemporary events, analyzes were made through documentation that has been the major source of evidence. Results: We identified in the municipality of San Carlos over the 10 years of activities related to social economy, a series of initiatives, these initiatives have occurred several actors for the purpose of promoting the solidarity economy, generating jobs and income and local development, these actors over the period channeled their actions to strengthen the theme in the city through meetings, forums and discussion spaces, yet they enable the institutionalization of this policy, which announced by the municipal government since 2001, included the solidarity economy in the public structure of municipal government , establishing a budget, as well as a legal and public spaces to establish partnerships marketing and development, which has made today the city is recognized for its activities and policies to promote the solidarity economy. Conclusion: it is necessary to further a series of actions in order to perpetuate, strengthen and expand the social economy initiatives in the city, given that they are still far from the desired character of transversality and announced by the municipal government, but what is fact is that initiatives to promote the solidarity economy are part of a program of government that has implemented policies of economic solidarity in the city in recent years, trying to generate work and income and local development, social inclusion and productive through the logic of solidarity and cooperation.